2016
DOI: 10.1016/j.nicl.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Alpha oscillation neurofeedback modulates amygdala complex connectivity and arousal in posttraumatic stress disorder

Abstract: ObjectiveElectroencephalogram (EEG) neurofeedback aimed at reducing the amplitude of the alpha-rhythm has been shown to alter neural networks associated with posttraumatic stress disorder (PTSD), leading to symptom alleviation. Critically, the amygdala is thought to be one of the central brain regions mediating PTSD symptoms. In the current study, we compare directly patterns of amygdala complex connectivity using fMRI, before and after EEG neurofeedback, in order to observe subcortical mechanisms associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 96 publications
(160 reference statements)
4
84
0
3
Order By: Relevance
“…Interestingly, these rt-fMRI results parallel those found with a different modality of neurofeedback (EEG), where one 30-minute session of alpha desynchronizing EEG-nf was shown to shift amygdala complex connectivity away from fear/defense processing and memory regions towards prefrontal emotion regulation areas after intervention [Nicholson et al, 2016b]. Further, consistent with our predictions, we found that PFC, rostral ACC, and insula activation was correlated negatively to PTSD dissociative symptoms during the transfer run.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Interestingly, these rt-fMRI results parallel those found with a different modality of neurofeedback (EEG), where one 30-minute session of alpha desynchronizing EEG-nf was shown to shift amygdala complex connectivity away from fear/defense processing and memory regions towards prefrontal emotion regulation areas after intervention [Nicholson et al, 2016b]. Further, consistent with our predictions, we found that PFC, rostral ACC, and insula activation was correlated negatively to PTSD dissociative symptoms during the transfer run.…”
Section: Discussionsupporting
confidence: 87%
“…Here, PTSD symptom severity positively correlated to the degree of amygdala downregulation during training runs 1 and 3, suggesting that patients with more severe PTSD symptoms actually decrease amygdala activity more during neurofeedback. Interestingly, these rt-fMRI results parallel those found with a different modality of neurofeedback (EEG), where one 30-minute session of alpha desynchronizing EEG-nf was shown to shift amygdala complex connectivity away from fear/defense processing and memory regions towards prefrontal emotion regulation areas after intervention [Nicholson et al, 2016b].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Studies utilizing EEG-nf for upregulation of alpha (or upper alpha) EEG power have demonstrated improvements in participants' cognitive and memory performance, including working memory and short term memory (Escolano et al, 2014;Hanslmayr, Sauseng, Doppelmayr, Schabus, & Klimesch, 2005;Hsueh, Chen, Chen, & Shaw, 2016;Nan et al, 2012;Zoefel, Huster, & Herrmann, 2011). Changes in resting fMRI functional connectivity following alpha EEG-nf training have also been reported (Kluetsch et al, 2014;Nicholson et al, 2016).…”
Section: Discussionmentioning
confidence: 99%